Innovation in social services : the public-private mix in service provision, fiscal policy and employment - Sirovátka, Tomáš; Greve, Bent (Ashgate Pub. Limited, 2014)
EU member states have seen high levels of unemployment in recent years especially amongst young people. At the same time the fiscal crisis of welfare states has made it difficult for them to invest in new jobs and new economic growth. The EU, at least since the enactment of the Amsterdam treaty, has had a focus on how to support member states' development of an employment policy which aims for higher levels of participation, lower levels of unemployment and more gender equal approaches. Through exploring patterns in the recent development of financing and governance of social services and de.